A Rare Presentation of Functional Movement Disorder Mimicking Normal Pressure Hydrocephalus - Onder, Halil; Ulker, Aycan Cemil; Comoglu, Selcuk (Asian Journal of Neurosurgery, 2024)
Herein, we describe a 55-year-old female patient with a functional movement disorder (FMD) who presented with normal pressure hydrocephalus (NPH)-like clinic. The neuroimaging data and positive response to the tap test initially suggested NPH. However, a detailed investigation of the clinic features yielded a final diagnosis of FMD. Via the presentation of this patient, we expand the phenomenology of FMD. To our knowledge, this is the first presentation of a patient with FMD mimicking NPH. Therefore, we think this rare illustration is interesting and may provide valuable perspectives for clinical practice.
Keywords: functional movement disorder; gait; CSF tap test; hydrocephalus; normal pressure hydrocephalus